2022
DOI: 10.1038/s41598-021-04502-2
|View full text |Cite
|
Sign up to set email alerts
|

The cyclic interaction between daytime behavior and the sleep behavior of laboratory dogs

Abstract: Sleep deprivation has been found to negatively affect an individual´s physical and psychological health. Sleep loss affects activity patterns, increases anxiety-like behaviors, decreases cognitive performance and is associated with depressive states. The activity/rest cycle of dogs has been investigated before, but little is known about the effects of sleep loss on the behavior of the species. Dogs are polyphasic sleepers, meaning the behavior is most observed at night, but bouts are also present during the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Living conditions in indoor areas as well as the impact of noisy nocturnal activity on the next day's behavior of diurnal animals is an understudied topic, typically not taken into account when assessing animal welfare in captivity. A recent study by Schork et al [30] investigated the effect of daytime activity on subsequent nocturnal activity and the effect of nocturnal activity on the next day's diurnal activity in laboratory-housed dogs. The findings in this study are consistent with those of our study on sanctuary chimpanzees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Living conditions in indoor areas as well as the impact of noisy nocturnal activity on the next day's behavior of diurnal animals is an understudied topic, typically not taken into account when assessing animal welfare in captivity. A recent study by Schork et al [30] investigated the effect of daytime activity on subsequent nocturnal activity and the effect of nocturnal activity on the next day's diurnal activity in laboratory-housed dogs. The findings in this study are consistent with those of our study on sanctuary chimpanzees.…”
Section: Discussionmentioning
confidence: 99%
“…The potential occurrence and likelihood of agonistic nocturnal interactions are expected to produce heightened alertness toward group members residing within the same night quarters. Although sleep in wild and captive chimpanzees tends to be frequently interrupted, it is likely that an increase in the number and intensity of these nocturnal disturbances may produce adverse effects on their physical and mental health, as well as their daytime behavior, as has been extensively studied in humans [7,11,27] and other non-human species [28][29][30]. Studies conducted on humans and laboratory animals demonstrated acute sleep deprivation to negatively affect mood and emotional wellbeing, as well as cognitive performance and motor functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dogs might get drowsy and irritable due to a lack of rest, like sleep deprived humans 42 , which can influence how they react to shelter staff or to new owners. Sleep deprived laboratory dogs showed behavioural changes, including increased inactivity (time spent laying and standing inactive), increased display of maintenance behaviours and decreased play and alert behaviours 43 . The relationship between sleep deprivation and the behaviour and mental state of sheltered dogs needs further study, as it may impact not only the welfare of dogs, but also the relationship with shelter staff and matching to potential adopters.…”
Section: Discussionmentioning
confidence: 99%
“…Scores for MCPQ-R were higher (except Neuroticism), whereas scores for DPQ were more spread out.6.1.3 Unit of Analysis.A typical way of capturing temporal dynamics in HCI and UbiComp studies is to use time windows at different times of day when calculating features[16,66,68,[91][92][93]. A large time window of eight hours, dividing the day into three periods, has been previously used in dog studies, and it has been found, for example, that studying night sleep separately from day sleep provided more meaningful insights about sleeping patterns[5,79] than studying sleeping during the whole day. Drawing from this prior line of work, we resorted to three time windows for our analysis: a) night (N): time from 12am to 5.59am; b) morning (M): time from 6am to 11.59am.…”
mentioning
confidence: 99%